Introducing the Value-Added Tax : Considerations for Implementation - Tadros, Farid (World Bank, Washington, DC, 2012)
Successfully implementing a value-added tax (VAT) system is complex and must be approached strategically and realistically in order to maximize company participation, create an efficient filing and audit administration, and encourage private sector growth. The active involvement of both the government and the private sector is essential to delivering sustainable results. This note presents the fundamentals of the VAT: how it works, the challenges of introducing it, a menu of good practice options, and lessons learned for implementation.